Attitudes to kidney donation among primary care patients in rural Crete, Greece - Chatziarsenis Marios; Tsafantakis Emmanouil; Alegakis Athanasios; Morgan Myfanwy; Antonakis Nikos; Komninos Ioannis D; Symvoulakis Emmanouil K; Philalithis Anastas; Jones Roger (BMC, 2009)
Abstract Background In Greece, there is limited research on issues related to organ donation, and the low rate of registration as donors requires explanation. This study reports the findings of a survey of knowledge and attitudes to kidney donation among primary care patients in rural Crete, Greece. Methods Two rural primary care settings in the island of Crete, Anogia Health Centre and Vrachasi Practice, were involved in a questionnaire survey. This was conducted among primary care patients (aged 18 years and over) with routine appointments, to assess their knowledge and attitudes to kidney donation. General practitioners (GPs) recruited patients and questionnaires were completed following the patients' medical consultation. Pearson's chi square tests were used and crude odds ratios (OR) with 95% confidence intervals (95% CI) were calculated in order to investigate into the possible associations between the respondents' knowledge, attitudes and specific concerns in relation to their socio-demographic features. Logistic regression analyses were used to examine differences by geographical location. Results The 224 (92.5%) of the 242 primary care attenders who were approached agreed to participate. Only 2.2% (5/224) of the respondents carried a donor card. Most participants (84.4%, 189/224) did not feel well informed about registering as a kidney donor. More than half of the respondents (54.3%, 121/223) were unwilling to register as a kidney donor and donate kidneys for transplant after death. Over a third of respondents (35.4%, 79/223) were not confident that medical teams would try as hard as possible to save the life of a person who has agreed to donate organs. People with a higher level of education were more likely to be willing to register as kidney donors [(OR: 3.3; 95% CI: 1.8-6.0), p < 0.001)] and to be less worried about their kidneys being removed after death [(OR: 0.3; 95% CI: 0.1-0.5), p < 0.001)] than those having a lower level of education. Conclusion Lack of knowledge and information regarding organ donation and negative attitudes related to registration as donors were the main findings of this study. Efforts should be based on targeting the attitudes to organ donation of individuals and population groups.